STRATEGI MENINGKATKAN LOYALITAS KONSUMEN MAKANAN KHAS KOTA CURUP KABUPATEN REJANG LEBONG - Sonatasia, Destri; Onsardi, Onsardi; Arini, Ety (Yayasan Insani Mandiri Santani, 2020)
The title of this study is the Strategy of Increasing Consumer Food Loyalty in Curup City, Rejang Lebong Regency (Case Study in